2022
DOI: 10.1177/87568705221094560
|View full text |Cite
|
Sign up to set email alerts
|

Exploring SWPBIS Implementation Outcomes in Rural and Urban Schools in Florida

Abstract: Rural schools experience unique challenges, including teacher quality and teacher retention, limited resources, and availability of funding. Furthermore, access to professional development and, subsequently, implementation of evidence-based practices may also be limited in rural settings. One evidence-based framework for implementing evidence-based practices, School-Wide Positive Behavioral Interventions and Supports (SWPBIS), has been widely implemented, including in rural and urban schools. Yet, very little … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
1
2

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 31 publications
1
1
2
Order By: Relevance
“…These results are different from those found by McIntosh et al (2016) and Gage et al (2022), who found no differences between rural and urban schools’ Tier 1 fidelity in Florida. We hypothesize that the different findings may be due to different measurement approaches or geographic differences.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…These results are different from those found by McIntosh et al (2016) and Gage et al (2022), who found no differences between rural and urban schools’ Tier 1 fidelity in Florida. We hypothesize that the different findings may be due to different measurement approaches or geographic differences.…”
Section: Discussioncontrasting
confidence: 99%
“…These results suggest that urban schools may need more training and support than rural schools overall, but particularly for advanced tiers. These results are different from those found by and Gage et al (2022), who found no differences between rural and urban schools' Tier 1 fidelity in Florida. We hypothesize that the different findings may be due to different measurement approaches or geographic differences.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations